The Effect Of Industry 4.0 Educational Literacy On Product Innovation Through Mediation Of Entrepreneur Mindset In MSMEs Bekasi City - Rany Cahyani; Dr. Suparno, S.Pd, M.Pd; Dr. Karuniana Dianta A. S, S.IP., M.E. (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
The Effect of Industry 4.0 Educational Literacy on Product Innovation Through Mediation of Entrepreneur Mindset in Umkm Bekasi City. Thesis. This study seeks to assess the impact of data literacy, human literacy, technological literacy on product innovation, through the mediation of the entrepreneur mindset of Bekasi City MSMEs. This study uses primary data through the Non-probability Purposive sampling method in the creative MSME sector in Bekasi City with a total sample of 319 MSMEs, through an independent survey with an online questionnaire. This research was conducted using quantitative descriptive methods, with the Structural Equation Model Partical Least Square (PLS-SEM) technique with the Smart-PLS application used to analyse the data. The results showed a positive and significant effect of data literacy, human literacy, technological literacy on product innovation through the mediation of entrepreneurial mindset. Data literacy variables play an important role in encouraging product innovation. MSMEs that are able to collect, analyse and utilise data well can identify market trends, consumer preferences and new opportunities more accurately, Human literacy, which includes the ability to think creatively, communicate and collaborate, is proven to have a positive impact on the quality of innovation. Technological literacy in the mastery of technology, such as the use of digital platforms for marketing, production automation, and data analysis, significantly improves the ability of MSMEs to produce innovative products. Entrepreneur mindset helps MSME actors to think creatively, be opportunity-orientated, and focus on innovative solutions.